Об экологии джунгарской гаички (Parus songarus Sеv.) - Ковшарь, А.Ф. (Вестник зоологии, 1976)
The nesting cycle of the dzhungarian tit was observed in 1971: 13 inhabited nests and 11 artificial nesting sites in the region of Bolshoe Almaatinskoe lake (Zailiisky Ala-tau, Tien Shan). Vocal activity, location and the process of nest building, the number of eggs in a clutch and duration of eggs incubation, details of nestlings rearing and after-nest life of broods are described. A low potential fertility (4-6 eggs in a clutch altogether) is compensated by a high survival rate of the progeny (not more than 18% of nests die).